Code Mixing in Sarah Sechan Talk Show Program - Dadan Hidayat; Chodidjah Chodidjah (Musamus Journal of Language and Literature, 2021)
Abstract- This research aimed to understand the categories of code mixing in Sarah Sechan programme. This research uses qualitative descriptive since the data collected were collected by watching the TV program. The data of this study was the sentences that contained code mixing within the extent of words, phrases, clauses or sentences which were found in utterances between the hosts and guests in Sarah Sechan program on Net TV. The source of information was Sarah Sechan talk show. The technique of data collection applies during this study was documentary technique and therefore, the instrument of information collection was recorder. The data was collected by downloading the video Sarah Sechan programme through official channel. Then, she transcribed each of the host and the guests’ utterances while they talked, commented, interacted and responded one another. After doing analyzing, the researcher roll out some facts. This type of insertion and external code mixing are dominant for this episode. Key words: Code Mixing, Sociolinguistic, Sarah Sechan Talk Show Program